The Role of Emotional Intelligence, Employee Engagement, and Psychological Well-being on Managerial Competence in Nonprofit Organizations - Dhia, Muhammad Rafi (Literacy: Journal of Education and Social Science, 2024)
This study explores the combined effects of emotional intelligence, employee engagement, and psychological well-being on managerial competence within nonprofit organizations. The sector's unique challenges necessitate effective management to balance mission-driven goals with organizational sustainability. Using a quantitative approach, data were collected from 160 managers through structured questionnaires. Multiple linear regression analysis, conducted using JASP software, revealed that emotional intelligence, employee engagement, and psychological well-being significantly predict managerial competence. The model with these predictors (M₁) explained 84.7% of the variance in managerial competence (R² = 0.849, Adjusted R² = 0.847) and demonstrated a substantial improvement over the baseline model (M₀) with an R² of 0.000. The coefficients for emotional intelligence (β = 0.450, t = 7.223, p < 0.001), employee engagement (β = 0.473, t = 7.826, p < 0.001), and psychological well-being (β = 0.465, t = 7.419, p < 0.001) were all highly significant. Among these, employee engagement had the strongest impact on managerial competence. The ANOVA test confirmed the model's robustness, with an F-value of 293.461 (p < 0.001), indicating that these variables collectively explain a significant portion of the variance in managerial competence. This study highlights the importance of integrating these factors to enhance managerial effectiveness in nonprofit settings.